A Cost Comparison of Organic and Conventional Apple Production in the State of Washington. Issue 1 (29th April 2013) - Taylor, Mykel; Granatstein, David
Abstract : Organic apple production expanded rapidly during the past decade due to strong demand, new technology, and price premiums, which suggests it is profitable for growers. No rigorous analysis of cost of production has been done to help project profitability in the face of continued increase in supply. The data presented here compare two methods of estimating cost of production and find that production of organic apples in Washington State, the leading producer, is approximately 5 to 10% more costly than conventional production on a per‐acre basis.